2008
DOI: 10.1080/13546780801934549
|View full text |Cite
|
Sign up to set email alerts
|

Rarity, pseudodiagnosticity and Bayesian reasoning

Abstract: Three experiments investigated the effect of rarity on people's selection and interpretation of data in a variant of the pseudodiagnosticity task. For familiar (Experiment 1) but not for arbitrary (Experiment 3) materials, participants were more likely to select evidence so as to complete a likelihood ratio when the initial evidence they received was a single likelihood concerning a rare feature. This rarity effect with familiar materials was replicated in Experiment 2 where it was shown that participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…By contrast, Feeney, Evans, and Venn (2008) showed that simply offering anchoring statistical information about a rare feature was enough to increase the rate of row choices. Our results corroborate and extend Feeney et al's findings and therefore also contrast with Evans et al's (2002) assumption by demonstrating that, once the relevance constraint is satisfied, reasoners can engage in diagnostic reasoning comparing values associated with a unique feature across alternative hypotheses even in the absence of explicit instructions to consider the alternative option.…”
Section: Dual-process Theorymentioning
confidence: 88%
“…By contrast, Feeney, Evans, and Venn (2008) showed that simply offering anchoring statistical information about a rare feature was enough to increase the rate of row choices. Our results corroborate and extend Feeney et al's findings and therefore also contrast with Evans et al's (2002) assumption by demonstrating that, once the relevance constraint is satisfied, reasoners can engage in diagnostic reasoning comparing values associated with a unique feature across alternative hypotheses even in the absence of explicit instructions to consider the alternative option.…”
Section: Dual-process Theorymentioning
confidence: 88%
“…The influence of the rarity of the absent clues Rarity effects concern the apportionment of increased attention to rare events in contrast to common ones (e.g., Feeney, Evans & Clibbens, 2000;Feeney, Evans & Venn, 2008;Green & Over, 2000;McKenzie & Mikkelsen, 2000Oaksford & Chater, 1994;2003;in legal contexts, for example, see Loftus, 1976;Wells & Lindsay, 1980). We included in our initial predictions a hypothesis that was based on rarity effects, conjecturing that participants would possibly pay more heed to absent clues when they were rare in comparison to present ones.…”
Section: Ancillary Findings: Possible Moderators Of the Feature-positmentioning
confidence: 99%
“…The above claims are supported by the following remarks. To begin with, the rare versus common feature manipulation along with the use of real-life contents produces departures from the uniformity assumption, as suggested by Feeney et al's (2008) manipulation check. For instance, in the "common" condition from their Experiment 2, Feeney et al identified average expected row values as varying from .49 to up to .92 across four problem contents, with average expected column/diagonal values concurrently ranging between .56 and .84.…”
Section: Nonstandard Versionsmentioning
confidence: 99%